Improving silage quality - K.K. Bolsen; Matthew A. Young; M.K. Siefers; G.L. Huck (Kansas Agricultural Experiment Station Research Reports, 1995)
Results at Kansas State University from over 200 laboratory-scale trials and 28 farmscale trials showed that bacterial inoculants consistently improved preservation efficiency and nutritive value of the ensiled material. In contrast, anhydrous ammonia or urea adversely affected dry matter recovery and production per ton of crop ensiled. Economic analysis also favored the use of bacterial inoculants over nonprotein-nitrogen additives. Research conducted using corn, sorghum, and alfalfa silages showed that sealing the exposed surface dramatically reduced top spoilage losses in bunker, trench, or stack silos.; Dairy Day, 1995, Kansas State University, Manhattan, KS, 1995;
Keywords: Dairy Day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-106-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 742; Silage; Inoculant; Nonprotein nitrogen; Top spoilage